2021
DOI: 10.1007/s11686-021-00470-9
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Assessment of Body Condition Score as a Possible Marker for the Targeted Selective Treatment of Dairy Sheep Against Gastrointestinal Nematodes

Abstract: Purpose In the fight against anthelmintic resistance, targeted selective treatments (TSTs), where only a small percentage of a flock receives treatment, have become increasingly popular. Overall, implementation of such treatments can be based on various parameters including Body condition score (BCS). As infection with non-bloodsucking nematodes, frequently encountered on sheep farms in the central Mediterranean basin, commonly causes bodyweight reduction, the aim of this research is to evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…and other non-bloodsucking nematodes known to reduce body weight (Bath et al ., 2001 ), but has been seen to have some limitations, such as the need to adapt the treatment threshold to the physiological (or productive) situation in a farm (Soto-Barrientos et al ., 2018 ; Aguirre-Serrano et al ., 2020 ). A study carried out in Sardinia Island (Tamponi et al ., 2022 ) aimed to evaluate the use of BCS as a marker of TST in lactating sheep in 2 different lactation periods (third and fifth month of lactation) by comparing BCS with FEC. The results of the study showed a negative correlation ( r = − 0.163) between EPG values and BCS of the studied animals, with the highest EPG values occurring in animals with the lowest BCS.…”
Section: Targeted Selected Treatmentmentioning
confidence: 99%
“…and other non-bloodsucking nematodes known to reduce body weight (Bath et al ., 2001 ), but has been seen to have some limitations, such as the need to adapt the treatment threshold to the physiological (or productive) situation in a farm (Soto-Barrientos et al ., 2018 ; Aguirre-Serrano et al ., 2020 ). A study carried out in Sardinia Island (Tamponi et al ., 2022 ) aimed to evaluate the use of BCS as a marker of TST in lactating sheep in 2 different lactation periods (third and fifth month of lactation) by comparing BCS with FEC. The results of the study showed a negative correlation ( r = − 0.163) between EPG values and BCS of the studied animals, with the highest EPG values occurring in animals with the lowest BCS.…”
Section: Targeted Selected Treatmentmentioning
confidence: 99%
“…Sixteen female Santa Inês adult sheep, multiparous, aged between two and five years, healthy, body weight from 30 to 40 kg, and mean body condition score of 3, considering a scale of 1-5 were used (Tamponi et al, 2021). The animals were kept on the premises of the Veterinary Hospital of the Institute of Veterinary Medicine, Federal University of Pará (IMEV/UFPA), in 16 m 2 collective pens, pre-adapted for 30 days, where they received grass cut from Pennisetum purpureum Schumach (Poaceae) daily, the variety was Cameron, balanced feed (Ovimax Campo, Qualy Nutrição Animal, SP, Brazil), ready-made mineral supplementation (Top Line Ovino, Matsuda, GO, Brazil), and water ad libitum.…”
Section: Animals and Study Groupsmentioning
confidence: 99%
“…Different types of questions were included, e.g., yes/no, single-and multiplechoice questions, open-ended questions, and questions with skip logic with a progression through the survey varying depending on the answer. The questionnaire consisted of nine subsections with general and specific questions about: (A) farm (1-13), (B) animals and housing (14)(15)(16)(17)(18)(19)(20)(21)(22), (C) biosecurity, hygiene, and animal purchases (23-32), (D) feeding (33)(34)(35)(36), (E) pasture management (37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51), (F) parasite management (52-65), (G) diagnostics and efficacy checks (66-72), (H) estimation (from the farmer's point of view) of parasitic diseases on the farm (73-75), and (I) voluntary participation in the clinical study (76).…”
Section: Questionnaire and Farm Selectionmentioning
confidence: 99%
“…These assessments are easy to implement and in most cases, (especially clinical examinations) are cost-effective [12,15,[17][18][19]. Clinical parameters are postulated to be associated to the number of excreted eggs [20][21][22]. However, this may depend on the prevailing nematode species, the host, age, nutrition, and environmental factors [19,23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation